Differentiated Learning Group Investigation Model to Improve Mathematics Learning Outcomes in Elementary Schools - Utami, Latisya; Surya Adikara, Fahmi; Susiloningsih, Esti (Universitas Negeri Surabaya, 2024)
Mathematics learning in elementary schools often faces challenges that cause students to have difficulties in understanding mathematical concepts which leads to low learning outcomes. This study aims to improve students' mathematics learning outcomes through the application of differentiated learning with a group investigation model. The research method used is classroom action research. The data collection techniques used in this study are observation, documentation and tests. The results in this study show that the learning outcomes of Mathematics of mean material have increased significantly. The results of the study prove that differentiated learning can improve Mathematics learning outcomes in elementary schools, especially in mean materials and data presentation. The results of the second cycle mean material mathematics test, students who scored above 70 or were declared complete amounted to 27 people with a percentage of 81.81%. The application of the group investigation model with a differentiated learning approach can be an alternative learning strategy that is effective in improving mathematics learning outcomes. The conclusion of the study is that differentiated learning by applying the group investigation model can improve mathematics learning outcomes in elementary schools.